Mesenchymal Stem Cells and Their Small Extracellular Vesicles as Crucial Immunological Efficacy for Hepatic Diseases - Tang, Yuting; Wu, Peipei; Li, Linli; Xu, Wenrong; Jiang, Jiajia (Frontiers in Immunology, 2022)
Mesenchymal stem cell small extracellular vesicles (MSC-sEVs) are a priority for researchers because of their role in tissue regeneration. sEVs act as paracrine factors and carry various cargos, revealing the state of the parent cells and contributing to cell–cell communication during both physiological and pathological circumstances. Hepatic diseases are mainly characterized by inflammatory cell infiltration and hepatocyte necrosis and fibrosis, bringing the focus onto immune regulation and other regulatory mechanisms of MSCs/MSC-sEVs. Increasing evidence suggests that MSCs and their sEVs protect against acute and chronic liver injury by inducing macrophages (MΦ) to transform into the M2 subtype, accelerating regulatory T/B (Treg/Breg) cell activation and promoting immunosuppression. MSCs/MSC-sEVs also prevent the proliferation and differentiation of T cells, B cells, dendritic cells (DCs), and natural killer (NK) cells. This review summarizes the potential roles for MSCs/MSC-sEVs, including immunomodulation and tissue regeneration, in various liver diseases. There is also a specific focus on the use of MSC-sEVs for targeted drug delivery to treat hepatitis.